Treatment Inertia and Symptom Burden in Anemia of CKD: Insights from the SATISFY Survey in the Middle East, South Africa, and Türkiye - Arici M; Al-Ghamdi SMG; Assounga AG; El-Koraie AF; McMillan A; Camidge LJ; Sumarsono B; Blogg M; Ng DB; Lansang EP (International Journal of Nephrology and Renovascular Disease)
Mustafa Arici,1 Saeed MG Al-Ghamdi,2 Alain G Assounga,3 Ahmed F El-Koraie,4 Abigail McMillan,5 Lucinda J Camidge,5 Budiwan Sumarsono,6 Martin Blogg,7 Daniel Bin Ng,6 Elvira P Lansang6 1Department of Nephrology, Hacettepe University Faculty of Medicine, Ankara, Türkiye; 2Department of Medicine, Nephrology Section, King Abdulaziz University and King Faisal Specialist Hospital & Research Center, Jeddah, Saudi Arabia; 3Department of Nephrology, Division of Medicine, University of KwaZulu-Natal, Durban, South Africa; 4Nephrology Unit, Alexandria Faculty of Medicine, Alexandria University, Alexandria, Egypt; 5Adelphi Real World, Bollington, UK; 6Astellas Pharma Singapore Pte. Ltd, Singapore, Singapore; 7Astellas Pharma Europe Ltd, Addlestone, UKCorrespondence: Mustafa Arici, Hacettepe University Faculty of Medicine, Department of Nephrology, Sihhiye, Ankara, 06100, Türkiye, Tel +90-312-324 3109, Fax +90-312-311 3958, Email marici@hacettepe.edu.tr, aricim@gmail.comIntroduction: Limited data exist regarding treatment patterns and symptom burden of patients with anemia of chronic kidney disease (CKD) in the Middle East, South Africa, and Türkiye.Methods: This real-world study explored clinical characteristics, symptom burden, and treatment patterns of patients with anemia of CKD living in the Middle East, South Africa, and Türkiye. Physician and patient perceptions of treatment were captured via cross-sectional surveys; patients’ clinical characteristics were recorded by retrospective review of medical records.Results: Data were collected from 1788 patients and 217 physicians. A high proportion of patients had never received treatment for their anemia (n = 701, 39.2%); the most common treatment was erythropoietin-stimulating agents (ESAs) + intravenous iron (n = 457, 50.3%). High symptom burden was reported, with lack of energy being the most common symptom (n = 394, 75.6% treated and n = 133, 59.9% non-treated patients). Patients’ self-reported symptom burden was higher than physician-reported burden; less agreement was seen for non-dialysis-dependent (NDD) patients (kappa = 0.193, standard deviation [SD]: 0.081) than dialysis-dependent (DD) patients (kappa = 0.442, SD: 0.103). Median hemoglobin thresholds that physicians reported using for initiating treatment (NDD: < 10.5 [interquartile range, 9.5– 12.0] g/dL; DD: < 9.3 [9.0– 10.0] g/dL) were higher than actual test levels at treatment initiation (NDD: 9.2 [8.7– 10.0] g/dL; DD: 9.0 [8.1– 10.0] g/dL).Conclusion: Treatment inertia is apparent despite high symptom burden in the Middle East, South Africa, and Türkiye, and disagreement was seen in physician and patient perspectives on symptomology. Improved awareness of this disagreement may help facilitate physician–patient dialogue to improve patient experience.Plain Language Summary: A survey to understand the experiences of people living with anemia and kidney disease in the Middle East, South Africa, and TürkiyeBackgroundPeople living with kidney disease can have a low number of red blood cells (anemia).This can cause heart problems, make kidney disease worse, and lead to death.Not much is known about the experiences of people living with kidney disease and anemia in the Middle East, South Africa, and Türkiye.For example, what symptoms do they experience, and which treatments do they receive for their anemia?What we didWe carried out surveys in the Middle East, South Africa, and Türkiye between June and September 2022.We surveyed 1788 people living with kidney disease and anemia, and 217 of their doctors.We asked about symptoms experienced by people living with kidney disease and anemia, and which treatments they received for their anemia.What we foundPeople living with kidney disease and anemia experienced many different symptoms.Lack of energy was the most common.People living with kidney disease and anemia mentioned symptoms more frequently than their doctors.Almost 40% of people living with kidney disease did not receive any treatment for their anemia.The most common treatment was iron combined with drugs that increase production of red blood cells (erythropoietin-stimulating agents).What does this mean?To improve communication and care, doctors should be made aware of how much the symptoms of anemia affect the lives of people living with kidney disease.Disclaimer: This plain language summary represents the opinions of the authors. For a full list of declarations, including funding and author disclosure statements, and copyright information, please see the full text online.Keywords: anemia, chronic kidney disease, treatment patterns, treatment satisfaction, symptom burden, real-world evidence